Predictors of cough-specific and generic quality of life in sarcoidosis patients - Gvozdenovic, Branislav S.; Mihailovic-Vucinic, Violeta; Vukovic, Mira; Stjepanovic, Mihailo; Buha, Ivana; Mihailovic, Strahinja V.; Maric, Nikola B. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2020)
Background: Cough is frequent symptom in sarcoidosis and its impact on patient’s quality of life (QoL) has not been adequately addressed so far. Objectives: The goal of this study was to determine the significant predictors of cough-specific and generic QoL in sarcoidosis patients. Methods: In the prospective study 275 sarcoidosis patients administered Patient Reported Outcomes instruments for measurement of dyspnea (Borg and MRC scales) and fatigue (Fatigue Assessment Scale (FAS) and Daily Activity List (DAL)), as well as patients’ QoL (cough-specific Leicester Cough Questionnaire (LCQ) and generic tool – 15D). The LCQ contains 3 domains covering physical, psychological and social aspects of chronic cough. Pulmonary function tests (spirometry and diffusing capacity for carbon monoxide) and serum angiotensin converting enzyme (sACE) were also measured. Results: Dyspnea measured by Borg scale and impairment of daily activities determined by DAL instrument as well as sACE were the strongest predictors of all cough-specific QoL domains. Mental aspect of patients’ fatigue was significantly correlated with all domains except with psychological LCQ domain. Regarding the generic QoL, the following significant predictors were: dyspnea measured by MRC scale, overall fatigue determined by FAS and physical domain of the LCQ. Conclusion: It is important to measure both cough-specific and generic QoL in sarcoidosis patients since they measure different health aspects and their predictors can be different. We demonstrated that physical domain of cough-specific QoL is significant predictor of generic QoL.